Target language use in teaching from the perspective of English teachers and student teachers in Finland - Rantala, Emma (My University, 2021)
This thesis examines English teachers and student teachers’ views on TL use in Finland. Target language (TL) is widely studied in the field of second language acquisition as teachers’ TL use is considered essential for students’ language learning. However, researchers do not have a consensus on whether the students’ first language (L1) should be used in foreign language teaching. In spite of the extensive research on TL, there is a gap in research on how English teachers and student teachers in Finland view their own TL use. The main research question of this thesis is: How do teachers and student teachers view target language use in a classroom? The supporting research questions are: What kinds of possible challenges there are in target language use for teachers and student teachers? In what kinds of functions do teachers and student teachers use target language in the classroom? How do teachers and student teachers’ views on target language use in a classroom differ from each other? The background theory consists of discussion of TL and L1, the language of classroom management, code-switching, and distinctive characteristics of teachers and student teachers’ TL use. The data were collected by interviewing four English teachers and three student teachers and the interviews were based on the themes that emerge in the background research for the topic. The data were analyzed using Schmidt’s (2004) strategy for analysis of semistructured interviews. The results showed that the teachers and student teachers view their own TL use as important for students’ learning. The main challenges that the participants identify in their TL use are the significant differences in students’ understanding of the TL, adapting their own TL use to these differences, and determining the amounts of TL and L1 use during a lesson. The functions in which the TL is used include giving basic instructions and greeting, whereas L1 is used for teaching grammar and giving complex instructions. The teachers and student teachers’ views on TL use differ in the aspects that are viewed as challenges in TL use. Furthermore, in relation to the challenges in TL use, the teachers are more focused on the students’ perspective on TL use, whereas the student teachers’ answers emphasize their own abilities as users of the TL. The results suggest that participants view teachers’ TL use as an important source of input for students and in spite of the challenging aspects of TL use, they have a positive attitude towards their own TL use. In the future, research could be conducted on whether new language teachers’ abilities to use the TL in their teaching could be improved by increasing the instruction of TL use in teacher training and university studies.
Keywords: target language, English as a foreign language, foreign language learning